Effect of Carrier Lipophilicity and Preparation Method on the Properties of Andrographolide-Solid Dispersion - Guowei Zhao; Qingyun Zeng; Shoude Zhang; Youquan Zhong; Changhao Wang; Yashao Chen; Liquan Ou; Zhenggen Liao (MDPI AG, 2019)
Solid dispersion (SD) is a useful approach to improve the dissolution rate and bioavailability of poorly water-soluble drugs. This work investigated the effects of carrier material lipophilicity and preparation method on the properties of andrographolide (AG)⁻SD. The SDs of AG and the carrier materials, polyethylene glycol (PEG) and PEG grafted with carbon chains of different length (grafted PEG), have been prepared by spray-drying and vacuum-drying methods. In AG⁻SDs prepared by the different preparation methods with the same polymer as carrier material, the intermolecular interaction, 5% weight-loss temperature, the melting temperature (Tm), surface morphology, crystallinity, and dissolution behavior have significant differences. In the AG⁻SDs prepared by the same spray-drying method with different grafted PEG as carrier material, Tm, surface morphology, crystallinity, and dissolution behavior had little difference. In the AG⁻SDs prepared by the same vacuum-drying method with different grafted PEG as carrier material, the crystallinity and Tm decreased, and the dissolution rate of AG increased with the increase of grafted PEG lipophilicity. The preparation method has an important effect on the properties of SD. The increase of carrier material lipophilicity is beneficial to the thermal stability of SD, the decrease of crystallinity and the increase of dissolution rate of a poorly water-soluble drug in the SD.